Developments in the Coordination Chemistry of Phosphinines (Eur. J. Inorg. Chem. 2/2013). Issue 2 (7th January 2013) - Müller, Christian; Broeckx, Leen E. E.; de Krom, Iris; Weemers, Jarno J. M.
Abstract : The cover picture shows examples of coordination compounds containing aromatic phosphorus heterocycles as ligands. It illustrates the most recent developments in the coordination chemistry of functionalized, π‐accepting phosphinines. Details are discussed in the Microreview by C.Müller et al. on p. 187 ff. This paper is dedictated to Prof. Dr. P.W.N.M. van Leeuwen on the occasion of his 70th birthday.